Narrating after “Centuria”: the mistaken and ‘impossible’ stories of “Tutti gli errori” - Andrea Gialloreto (Finzioni, 2023)
After experimenting the serial variations of micro-stories with Centuria, Manganelli moved away from the short-form option shared with authors such as Calvino, Parise, Wilcock and Malerba to undertake with Tutti gli errori (1986), his last collection of short stories, a reflection on literary genres and narrative conventions that is confirmed in the theoretical pages of the essay Che cosa non è un racconto, from the book Il rumore sottile della prosa (1994). The article proceeds to an analysis of the transformations that the structure of the impossible or erroneous tale inflicts on classic motifs of Manganelli’s imagery such as the infernal journey, asymmetrical love, the haunted mansion, and the descendent nature of man.